2014
DOI: 10.1016/j.jcrs.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable intraocular lens power technology

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 39 publications
0
56
0
Order By: Relevance
“…Incorrect lens power, patient dissatisfaction, and IOL opacification are common reasons for IOL replacement . Despite advances in biometry and IOL calculations, Behndig et al showed in a large analysis of Swedish cataract surgical outcomes that only two thirds of eyes planned for emmetropia become emmetropic .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorrect lens power, patient dissatisfaction, and IOL opacification are common reasons for IOL replacement . Despite advances in biometry and IOL calculations, Behndig et al showed in a large analysis of Swedish cataract surgical outcomes that only two thirds of eyes planned for emmetropia become emmetropic .…”
Section: Discussionmentioning
confidence: 99%
“…Almost 1% of cataract surgery patients will eventually require an intraocular lens (IOL) exchange . While IOL dislocation/decentration is the most common reason for IOL exchange, ranging between 37.3% and 46% of the cases, incorrect IOL power (23–41.2%), IOL opacification (7%) and patient dissatisfaction (21%) are other common causes . Furthermore, patient expectations are increasingly high, especially with increased use of premium IOLs .…”
Section: Introductionmentioning
confidence: 99%
“…To avoid these postoperative problems, a potential alternative is the use of an adjustable IOL. Many mechanically and magnetically adjustable IOLs were patented or described in the literature . However, these lenses have some disadvantages such as invasive adjustment procedures and incompatibility with imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, several noninvasive adjustable IOLs have been reported in literature. Sacharoff et al and Bille have developed IOLs that are postoperatively adjustable by femtosecond laser . These IOLs consist of an optic containing thin layers of shape‐altering material, which change shape and cause the optic change after activation by femtosecond laser.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation